TINJAUAN YURIDIS TERHADAP PERALIHAN KEPEMILIKAN SAHAM SECARA DIAM-DIAM (STUDI PADA PUTUSAN NO. 1130/K/Pdt/2010) - LESTARI SEMBIRING MEILALA (PREMISE LAW JURNAL, 2015)
Transfers of shares carried out in a PT is through buying and selling, there is a difference between the PT closed with PT open. PT enclosed in buying and selling shares is done by the determination of the statutes and policies determined by the shareholders. In a Limited Liability Company transfers of shares may take place silently in which the events are there is a debtor's shares have been sold without the lender without the knowledge sidebitur. Therefore, the researchers looked at the need to do further research on the transfer of ownership of shares in a limited liability company. The issues raised in this research are: first, how the transfer of rights to shares in the Company Limited. Secondly, what is the legal effect of the transferred shares secretly on limited liability. Third, how is the decision of the court on the case of the decision No. 1130 / K / Pdt / 2010. To examine the above matters, conducted research that is descriptive analysis. Method research approach is normative juridical approach. This study uses secondary data consisting of primary legal materials, legal materials and secondary legal materials tertiary. From the research, it can be concluded, first, the transfer of shares is done through a deed of transfer of rights. It is stipulated in Article 56 of Law No. 40 of 2007 on Limited Liability Company. Second, the transfer of tacit on this stock will have an impact over the ownership of shares in which an individual or other legal entity has the right and responsibility for its shares. Third, if the Board of Directors in carrying out its authority should not violate the principle of breach of trust by default in carrying out the duties and responsibilities for the care of the company, the Board of Directors may take advantage of the Law of Corporations in the United States. This concept prevents the courts in the United States to question the business decision-making by the Board of Directors, which is taken in good faith for the defense of himself when he was accounted for in the management of the company. Keywords: Transfer of Rights Shares, Shares Transition Secretly, Decision No. 1130/K/Pdt/2010